Enhancing Immunization Rates through Pharmacist Involvement - alshammari, Saad khalaf; Alsaqr, Sultan Mohammed; alotaibi, Mishal Khaled; Alanazi, Ahmed Murdhi Mohammed; Alotaibi, Abdulaziz Abdullah S; Matar, Abdullah Salman Mohammed; Alharbi, Waleed Farah (Journal of Posthumanism, 2025)
Pharmacists and student pharmacists have the potential to improve immunization rates in many communities and patient populations. Pharmacists, in particular, are expected to play a valuable role in increasing adult vaccination rates. Therefore, evidence-based and relevant strategies to confirm immunization history, recommend necessary vaccines, and then efficiently and effectively provide these vaccines are of importance. Such strategies can greatly increase patient, caregiver, and healthcare provider confidence in vaccination and vaccination recommendations.